Resistive state relaxation time in ZrO2(Y)-based memristive devices under the influence of external noise. (September 2022) - Koryazhkina, M.N.; Filatov, D.O.; Shishmakova, V.A.; Shenina, M.E.; Belov, A.I.; Antonov, I.N.; Kotomina, V.E.; Mikhaylov, A.N.; Gorshkov, O.N.; Agudov, N.V.; Guarcello, C.; Carollo, A.; et al.
Abstract: The effects of external digitally synthesized Gaussian noise on the resistive state relaxation time of a ZrO2 (Y)-based memristive device when switching from a low resistance state to a high resistance state have been experimentally investigated. A nonmonotonic dependence of the resistive state relaxation time on the external noise intensity is found. This behavior is interpreted as a manifestation of the noise-enhanced stability effect previously observed in various complex systems with metastable states. It is shown that the experimental results agree satisfactorily with the theoretical ones. The presented results indicate the constructive role of external noise and its possible use as a mechanism for controlling the kinetics of resistive switching.